RAISE: A Resistive Accelerator for Subject-Independent EEG Signal Classification - Chen, Fan; Song, Linghao; Li, Hai Helen; Chen, Yiran (Proceedings - Design, Automation, and Test in Europe Conference and Exhibition, 2021)
State-of-the-art deep neural networks (DNNs) for electroencephalography (EEG) signals classification focus on subject-related tasks, in which the test data and the training data needs to be collected from the same subject. In addition, due to limited computing resources and strict power budgets at edges, it is very challenging to deploy the inference of such DNN models on biological devices. In this work, we present an algorithm/hardware co-designed low-power accelerator for subject-independent EEG signal classification. We propose a compact neural network that is capable to identify the common and stable structure among subjects. Based on it, we realize a robust subject-independent EEG signal classification model that can be extended to multiple BCI tasks with minimal overhead. Based on this model, we present RAISE, a low-power processing-in-memory inference accelerator by leveraging the emerging resistive memory. We compare the proposed model and hardware accelerator to prior arts across various BCI paradigms. We show that our model achieves the best subject-independent classification accuracy, while RAISE achieves 2.8× power reduction and 2.5× improvement in performance per watt compared to the state-of-the-art resistive inference accelerator.